U JI VALIDITAS ISI (CONTENT VALIDITY) ALAT UKUR KECERDASAN EMOSIONAL TARUMANAGARA - Felita Oktaviani; P. Tommy Y. S. Suyasa (PROSIDING SERINA, 2021)
In everyday life, humans can feel various emotions from the events they experience. These emotions include anger, sadness, fear, pleasure, love, surprise, annoyance, and embarrassement. With the existence of various emotions, humans need to have the ability to know and regulate the emotions of themselves and others, as well we utilizing the emotions. These abilities are called the emotional intelligence. Emotional intelligence has an important role in everyday life, including in social, educational, and work contexts. Knowing the importance of emotional intelligence, an emotional intelligence test is needed, especially for Indonesians. This study aims to produce an emotional intelligence test that has a good content validity. Alat Ukur Kecerdasan Emosional Tarumanagara is designed with reference to the emotional intelligence test that has been widely used and has a good reliability, namely the Schutte Self-Report Emotional Intelligence Test (SSEIT). Each item was reviewed by five experts with certain criteria. Based on the expert judgment, there are two items that need to be eliminated because they are considered less relevant to measure emotional intelligence. The result of this study recommends Alat Ukur Kecerdasan Emosional Tarumanagara which consists of 33 items with 10 items measuring emotion perception, 8 items measuring own emotion regulation, 7 items measuring others emotion regulation, and 8 items measuring emotion utilization.